2008
DOI: 10.1038/onc.2008.305
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of apoptosis by PML and the PML-NBs

Abstract: The promyelocytic leukemia protein (PML) is a tumor suppressor identified in acute PML and implicated in the pathogenesis of a variety of tumors. PML is essential for the proper assembly of a nuclear macromolecular structure called the PML nuclear body (PML-NB). PML and PML-NBs are functionally promiscuous and have been associated with the regulation of several cellular functions. Above all these is the control of apoptosis, a function of PML whose physiological relevance is emphasized by in vivo studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 102 publications
2
99
0
3
Order By: Relevance
“…Loss of PML sensitizes mice to physically and chemically induced tumorigenesis. This sensitization correlates with defects of PML Ϫ/Ϫ mouse embryo fibroblasts (MEFs) in apoptotic responses to stimuli such as type I and II interferons, gamma radiation, and ceramide (6,7). Additionally, several mouse models of cancer have shown that loss of PML sensitizes mice to increased tumorigenesis, whereas increased expression of PML has a preventative effect on tumor growth (8 -13).…”
mentioning
confidence: 99%
“…Loss of PML sensitizes mice to physically and chemically induced tumorigenesis. This sensitization correlates with defects of PML Ϫ/Ϫ mouse embryo fibroblasts (MEFs) in apoptotic responses to stimuli such as type I and II interferons, gamma radiation, and ceramide (6,7). Additionally, several mouse models of cancer have shown that loss of PML sensitizes mice to increased tumorigenesis, whereas increased expression of PML has a preventative effect on tumor growth (8 -13).…”
mentioning
confidence: 99%
“…It is a key constituent of the punctate nuclear structures known as PML-nuclear bodies (PML-NB) (Ascoli and Maul, 1991;Lamond and Earnshaw, 1998;Ishov et al, 1999;Bernardi et al, 2008). It has been shown that sumoylation is required for PML to form mature nuclear bodies (PML-NBs) (Kamitani et al, 1998;Zhong et al, 2000a;Eskiw et al, 2004;Shen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…12 A possible explanation for why Pml null cells are resistant to many apoptotic stimuli can be ascribed to the fact that PML can act as a pleiotropic factor in the functional regulation of several pro-and antiapoptotic factors. 13 Indeed, PML is functioning as part of a complex tumorsuppressive network. For instance, it is well established that PML is an important factor in the regulation of both p53-dependent and -independent apoptotic pathways.…”
Section: The Promyelocytic Leukemia Proteinmentioning
confidence: 99%
“…For instance, it is well established that PML is an important factor in the regulation of both p53-dependent and -independent apoptotic pathways. 13,14 PML activates p53 by several means: by recruiting p53 to PML-NBs by promoting its acetylation and phosphorylation, [15][16][17][18] and by binding and inhibiting Mdm2, the main negative regulator of p53, [19][20][21] as well as by promoting p53 de-ubiquitination by the ubiquitin protease HAUSP. 22,23 Moreover, PML can act as a suppressor of other major oncogenic pathways, such as the PI3K/Akt pathway, through its ability to interact with the protein phosphatase PP2A and inhibit the nuclear function of Akt, thus leading to suppression of its prosurvival and promitogenic functions.…”
Section: The Promyelocytic Leukemia Proteinmentioning
confidence: 99%